Comparison of Visual Outcomes and Quality of Life in Patients with High Myopic Cataract after Implantation of AT LISA Tri 839MP and LS-313 MF30 Intraocular Lenses. (28th February 2022) - Shen, Jiying; Zhang, Limei; Ni, Shuang; Cai, Lei; Guo, Haike; Yang, Jin
Abstract : Purpose . To investigate the benefits of multifocal lens in patients with high myopic cataract and compare the clinical effects between AT LISA tri 839MP and MPlus LS-313 MF30 intraocular lenses (IOLs) in high myopic eyes. Methods . This retrospective cohort study analyzed 60 eyes with axial length >26 mm in 40 patients. Thirty eyes were implanted with MF30, and the remaining 30 eyes were implanted with 839MP. Postoperative uncorrected distance visual acuity (UDVA), best corrected distance visual acuity (BCDVA), uncorrected intermediate visual acuity (UIVA) and uncorrected near visual acuity (UNVA), defocus curve, modulation transfer function (MTF) curve, Strehl ratio (SR), and complications were compared between the two groups. Results . All vision outcomes were significantly improved in both groups (p < 0.05 ). There was no significant between-group difference in UDVA at 1 and 3 months postoperatively (p > 0.05 ). However, UIVA and UNVA were significantly better in the 839MP group (p < 0.05 ). The VF-14 score, especially for near vision quality, was significantly higher in the MF30 group (2.2 ± 0.9 vs. 0.8 ± 0.7; p ≤ 0.001 ). The SR of both groups significantly increased postoperatively (p < 0.05 ). All the 3-month MTF curve values (MTF 10 total, MTF 10 internal, MTF 30 total, and MTF 30 internal) were significantly better in the 839MP group (p < 0.05 ). Meanwhile, all the high-order aberration values (coma, spherical aberration, and trefoil) were significantly greater in the MF30 group (p < 0.05 ). Conclusion . Multifocal IOL implantation achieves good quality of distance, intermediate, and near vision in patients with high myopia, improving their quality of life. Both 839MP and MF30 IOLs can provide good distance vision, but 839MP performs better in near and intermediate vision. However, for some patients with an extra-long optic axis, MF30 may be a good choice because of its wider range of degrees.